A low-temperature preparation method for TiO2@SiO2 core-shell structured materials and its application methods

CN122326019BActive Publication Date: 2026-10-20JINGDEZHEN CERAMIC UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202610787950.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-03
Publication Date
2026-10-20
Estimated Expiration
2046-06-03

AI Technical Summary

Technical Problem

[0005]综上所述,现有TiO2@SiO2核壳结构的制备方法主要存在以下技术问题:液相法难以实现壳层厚度调控及连续致密包裹,高温处理能耗高且易导致粉体烧结,原子层沉积法设备昂贵、难以规模化应用

Benefits of technology

(1)实现单核致密包裹与厚度精准可控:本发明针对现有技术中普遍存在的“多核团聚”与“包裹层疏松”的技术痛点,创新性地提出了“双重表面添加剂预处理+梯度反应工艺”策略。通过六偏磷酸钠与硅烷偶联剂的协同作用,在TiO2表面接枝大量活性化学锚定位点,并利用硅烷长链的空间位阻效应维持了颗粒在液相体系中的高度单分散状态。配合“梯度滴加”工艺,精确控制反应体系处于极低的过饱和度,从根源上抑制SiO2的自成核,确保硅源仅在TiO2表面发生异相成核生长,形成致密的SiO2包裹层。该工艺实现了接近100%的单核包裹率,并建立了包裹层厚度与硅源用量的定量关系模型,实现了在5~40nm范围内对壳层厚度的纳米级精准调控(实测包覆层厚度与目标值偏差<8%),解决了现有技术中包裹层厚度不可控、易形成多核包裹的共性难题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122326019B_ABST
    Figure CN122326019B_ABST
Patent Text Reader

Abstract

The application discloses a low-temperature preparation method of TiO2@SiO2 core-shell structure material and an application method of a product thereof. Firstly, TiO2 powder is treated by a sodium hexametaphosphate and silane coupling agent solution to obtain high-dispersion active TiO2 powder; then, in a water-ethanol system, the reaction concentration of tetraethyl orthosilicate is accurately controlled by a flow pump, and stable TiO2@SiO2 core-shell structure powder is prepared through aging, washing and low-temperature drying. By optimizing the proportion of reactants and process conditions, the single core coating with a thickness-adjustable SiO2 coating layer, high coating rate and compact structure is realized. The obtained core-shell material is applied to photovoltaic glass ink, and can significantly improve the reflectivity and durability of the coating. The whole preparation process is mild in conditions, simple in operation, good in repeatability, easy to popularize in scale, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of glass ink technology, and in particular to a low-temperature preparation method for TiO2@SiO2 core-shell structured materials and the application method of the products thereof. Background Technology

[0002] With the rapid development of photovoltaic power generation technology, double-glass photovoltaic modules have gradually become the mainstream in the market due to their excellent lifespan and power generation efficiency. To further improve the photoelectric conversion efficiency of the modules, a layer of high-reflectivity white ink is usually printed on the inner surface of the photovoltaic backsheet glass. The main function of this coating is to reflect sunlight passing through the gaps between the cells back to the cell surface for secondary utilization. TiO2, due to its extremely high refractive index and excellent whiteness, is currently the most ideal white pigment for photovoltaic glass inks. However, because TiO2 has photocatalytic activity, under long-term outdoor sunlight exposure, the generated photogenerated electrons and holes can induce redox reactions. On the one hand, the Ti in the crystal lattice... 4+ Easily reduced to Ti 3+ The generation of oxygen vacancies leads to the formation of significant absorption centers in the material, causing yellowing of the coating. Furthermore, photogenerated carriers attack and disrupt the silicon-oxygen network structure of the inorganic glass flux, resulting in decreased strength and adhesion of the coated glass network structure, ultimately leading to powdering and peeling. Simultaneously, photovoltaic modules are prone to potential-induced degradation (PID) under high temperature and humidity environments, causing a significant decrease in the output power of solar cells. Therefore, coating the TiO2 surface with a dense, chemically inert insulating layer of SiO2 to block its photocatalytic activity and improve acid and alkali resistance is key to solving these problems.

[0003] Currently, while there has been considerable research on the surface coating modification technology of inorganic powders, several technical bottlenecks remain in the application field of photovoltaic glass inks. Traditional liquid-phase coating processes struggle to achieve monodisperse, single-core encapsulation. Chinese patent CN201110258959.1 discloses a non-hydrolyzed sol-gel method for preparing encapsulated pigments. Although this simplifies the process, such methods typically involve coating in a particle-agglomerated state, easily forming a "dumpling-like" multi-core encapsulation structure. This structure not only makes it difficult to uniformly control the coating thickness but also significantly reduces the specific surface area of ​​the pigment due to the multi-core agglomerates. To obtain a dense coating layer, existing technologies often rely on high-temperature processing. Chinese patent CN202410145016.5 discloses a method for preparing ceramic encapsulated pigments with monocore encapsulation and controllable coating thickness. While this method achieves a relatively good monocore structure through autocatalytic reaction, it requires high-temperature calcination at 900–1200℃ in a non-oxidizing atmosphere to form a dense NaAlSiO4 coating layer, a high-temperature process with enormous energy consumption. While vapor deposition technology can prepare dense and uniform coating layers, it is costly. Chinese patent CN202511218982.6 proposes to deposit SiO2 layers on the surface of ceramic powder using physical vapor deposition or chemical vapor deposition. Although the coating layer obtained by this method is dense and uniform, it relies on expensive vacuum equipment, and it is difficult to achieve large-scale, continuous, uniform deposition on substrates with huge specific surface areas such as powder. The high preparation cost limits its industrial application in the field of photovoltaic glass ink fillers.

[0004] The composite structure of TiO2 and SiO2 has a dual effect on the photocatalytic activity of TiO2, either "promoting" or "inhibiting" it. The core of this effect depends on the interfacial contact state and coating morphology of the two materials. In existing technologies, discontinuous or non-core-shell TiO2-SiO2 composite materials are often used. Literature (DOI:10.1007 / s11356-022-18793-z; DOI:10.3389 / fchem.2021.738969; DOI:10.1016 / j.jhazmat.2009.09.108; DOI:10.1016 / j.apcatb.2013.01.021) reports the synthesis of TiO2-SiO2 composite materials. Although this type of composite introduces the inert material SiO2, its main function is to improve the dispersibility of TiO2 and significantly increase the specific surface area and adsorption sites, thus significantly enhancing the photocatalytic effect of TiO2. To effectively suppress the photocatalytic activity of TiO2, a liquid-phase chemical method is mainly used to prepare TiO2@SiO2 core-shell structures. The aim is to utilize the formed dense SiO2 coating layer as an electronic and physical shielding layer to completely block the migration of TiO2 photogenerated carriers. However, existing preparation processes generally suffer from the following technical bottlenecks, making it difficult to meet the stringent requirements for material performance and cost in applications such as photovoltaic glass inks: the reaction kinetics of conventional liquid-phase processes are difficult to control, resulting in uncontrollable morphology and density of the coating layer. The literature (DOI:10.5012 / BKCS.2012.33.11.3767; DOI:10.3390 / cryst10020080; DOI:10.1039 / C6RA28098F; DOI:10.1016 / j.ceramint.2024.02.011; DOI:10.1002 / sia.2313) reports a stirring process in which tetraethyl orthosilicate is directly added to a water / ethanol solution containing TiO2. Although this method is simple to operate, the lack of steric hindrance in the reaction system makes it impossible to effectively control the hydrolysis-condensation rate of the silicon source, leading to a high supersaturation state. This easily causes two problems: first, SiO2 undergoes homogeneous self-nucleation, forming free SiO2 particles; second, multiple TiO2 particles are simultaneously encapsulated, forming multinucleated aggregates. Even when a coating layer is formed, its structure is often loose and porous, making it impossible to quantitatively control the shell thickness and resulting in unstable inhibition of TiO2 photocatalytic activity. Based on the above stirring process, the literature (DOI:10.1016 / j.electacta.2014.03.032) added tetraethyl orthosilicate to a TiO2-containing water / ethanol solution, stirred it, and then transferred it to a reactor for hydrothermal reaction, obtaining TiO2@SiO2 core-shell structured powder with a dense coating layer and good dispersibility. However, this method requires a reactor, resulting in high costs and limiting its large-scale application in actual production.To address the aforementioned issues, some studies have attempted to utilize alternative silicon sources. The literature (DOI:10.1021 / acsomega.3c02679) uses sodium silicate nonahydrate as the silicon source to prepare TiO2@SiO2 materials. While this method can achieve SiO2 deposition on the TiO2 surface, it still suffers from the following drawbacks: First, it lacks a precise thickness control model, making it difficult to quantitatively regulate the coating thickness; second, SiO2 particles randomly accumulate on the TiO2 surface, easily forming discontinuous "island" structures or densely packed particle layers, making it difficult to achieve continuous and dense mononuclear coating. This non-dense coating layer cannot completely block the photocatalytic activity of TiO2, and it is difficult to simultaneously achieve both optical performance and coating effectiveness. To solve the problem of coating layer density, some studies have introduced post-processing techniques. The literature (DOI:10.1016 / j.colsurfa.2004.10.014) prepared TiO2@SiO2 in an acetone / ethanol system, but a dense SiO2 coating layer could only be obtained by high-temperature calcination at 800℃. This process has significant drawbacks: high-temperature treatment is not only energy-intensive but also prone to secondary sintering and hard agglomeration of powder particles, damaging the material's dispersibility and affecting its final performance. In recent years, atomic layer deposition (ALD) has been used to prepare TiO2@SiO2 materials. The literature (DOI:10.1016 / j.ceja.2022.100288) used this method to deposit a very thin and dense SiO2 layer on the TiO2 surface with ideal coating effect. However, this technology has the following limitations: it is highly dependent on expensive vacuum deposition equipment, and the process flow is complex; it is difficult to achieve continuous and uniform large-scale deposition on powder substrates with huge specific surface areas. The high preparation cost makes it impractical for industrial applications such as photovoltaic glass inks.

[0005] In summary, existing methods for preparing TiO2@SiO2 core-shell structures mainly suffer from the following technical problems: liquid-phase methods struggle to achieve controlled shell thickness and continuous, dense encapsulation; high-temperature processing is energy-intensive and prone to powder sintering; and atomic layer deposition (ALD) methods are expensive and difficult to scale up. Therefore, developing a simple, cost-effective, and adjustable-shell-thickness low-temperature preparation method is crucial for promoting the industrial application of TiO2@SiO2 core-shell materials in the photovoltaic field. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a low-temperature preparation method for TiO2@SiO2 core-shell structured materials with low cost, simple process, and excellent performance, as well as the application method of the products thereof.

[0007] This invention is achieved through the following technical solution: A low-temperature preparation method for TiO2@SiO2 core-shell structured materials, characterized by comprising the following steps: Step 1: According to the mass ratio of rutile TiO2, sodium hexametaphosphate, water, and silane coupling agent 1:0.005~0.01:15~20:0.01~0.02, first add rutile and sodium hexametaphosphate to water for ultrasonic treatment and stirring dispersion to obtain TiO2 aqueous suspension. Then, add silane coupling agent-ethanol dilution solution dropwise to the stirred TiO2 aqueous suspension using a flow pump. After the addition is complete, adjust the pH value to the appropriate value with dilute hydrochloric acid, continue stirring and aging for 1~2 hours, wash with ethanol, filter, and freeze dry to obtain highly dispersed active TiO2 powder. Step 2: Add the highly dispersed active TiO2 powder obtained in Step 1 to a water-ethanol mixed solution and stir to disperse it, thereby obtaining a TiO2 water-ethanol suspension. Then, according to the mass ratio of highly dispersed active TiO2 powder to tetraethyl orthosilicate 1:0.16-1.54, add the tetraethyl orthosilicate-ethanol dilution to the stirred TiO2 water-ethanol suspension using a gradient dropwise process. After the dropwise addition is complete, adjust the pH value to the appropriate value with ammonia water. Then, after stirring and aging, washing, and low-temperature drying, obtain stable TiO2@SiO2 core-shell structure powder. In step two, the gradient dripping process involves pausing for 5 to 10 minutes after each drop of 25% of the total volume of the tetraethyl orthosilicate-ethanol diluent is added, and then continuing to add at a rate of 0.1 to 0.7 ml / min. This cycle is repeated until all the drops are added.

[0008] In step one, the mass ratio of silane coupling agent to ethanol in the silane coupling agent-ethanol dilution solution is 1:3 to 5; the average size of the highly dispersed active TiO2 powder particles is 350 nm.

[0009] The ultrasonic treatment time in step one is 15-20 min, the stirring time is 15-20 min, the dropping rate of the silane coupling agent-ethanol dilution is 0.2-0.5 ml / min, and the pH value is 4-6.

[0010] In step two, the volume ratio of water to ethanol in the water-ethanol mixed solution is 1:3 to 8, the volume ratio of ethanol to tetraethyl orthosilicate in the tetraethyl orthosilicate-ethanol dilution is 4:1, the pH value is 9 to 10, the stirring and aging time is 10 to 16 hours, the drying temperature is 150 to 200°C, and the drying time is 10 to 15 hours.

[0011] The method for applying the product obtained by the aforementioned method is characterized by comprising the following steps: Step 1: According to the glass flux formula, K2O 0-6 mol%, Na2O 2-6 mol%, CaO 0-4 mol%, BaO 0-3 mol%, ZnO 28-46 mol%, B2O3 15-18 mol%, Bi2O3 2-17 mol%, SiO2 16-35 mol%, Al2O3 1-2 mol%, the raw materials are mixed, melted, and cooled to obtain ZnO-B2O3-Bi2O3-SiO2 glass frit. The glass frit is then crushed, ball-milled, and passed through a 250-mesh sieve to obtain low-melting-point glass powder. Step 2: Mix low melting point glass powder, ink oil and TiO2@SiO2 core-shell structure powder in a certain mass ratio, grind and pass through a 250-mesh sieve to obtain glass ink; Step 3: The glass ink obtained in Step 2 is printed onto a glass substrate using a 200-mesh screen printing machine. The glass substrate is then fired at 670-750°C and held at the highest temperature for 90-200 seconds to obtain glass with an inorganic high-reflectivity coating.

[0012] The melting process in step one is carried out at a temperature of 1200–1280℃ for 2–4 hours; the resulting low-melting-point glass powder has a coefficient of thermal expansion α of 5.26–8.96 × 10⁻⁶ at room temperature to 300℃. -6 K -1 Softening temperature T f The temperature ranges from 500 to 595℃.

[0013] In step two, the mass percentages of low-melting-point glass powder, ink oil, and TiO2@SiO2 core-shell structure powder are 45-65:15-32:19-40; the ink oil is a water-based ink oil.

[0014] The water-based ink oil comprises, by weight percentage, the following components: 15-35% water-based acrylic resin, 5-10% polyvinyl alcohol, 5-15% propylene glycol, 0.1-1% polyether-modified siloxane, 0.1-0.5% ammonia, with the balance being water.

[0015] The reflectivity range of the inorganic high-reflectivity coating in step three is 90.2% to 95.1%.

[0016] The present invention has the following beneficial effects: (1) Achieving dense mononuclear encapsulation and precise thickness control: This invention addresses the technical pain points of "multinuclear agglomeration" and "loose encapsulation layer" commonly found in existing technologies by innovatively proposing a "dual surface additive pretreatment + gradient reaction process" strategy. Through the synergistic effect of sodium hexametaphosphate and silane coupling agent, a large number of active chemical anchoring sites are grafted onto the TiO2 surface, and the steric hindrance effect of the long silane chain is used to maintain the highly monodisperse state of the particles in the liquid phase system. Combined with the "gradient drop addition" process, the reaction system is precisely controlled to be at an extremely low supersaturation, which fundamentally inhibits the self-nucleation of SiO2 and ensures that the silicon source only undergoes heterogeneous nucleation growth on the TiO2 surface, forming a dense SiO2 encapsulation layer. This process achieves a near 100% single-core encapsulation rate and establishes a quantitative relationship model between the encapsulation layer thickness and the amount of silicon source used. It enables precise nanoscale control of the shell thickness within the range of 5–40 nm (the measured encapsulation layer thickness deviates from the target value by <8%), solving the common problems of uncontrollable encapsulation layer thickness and easy formation of multi-core encapsulation in existing technologies.

[0017] (2) Low-temperature densification technology without high-temperature calcination: In traditional coating processes, the SiO2 and TiO2 cores are mainly bonded by weak van der Waals forces or hydrogen bonds, requiring high-temperature calcination at >800℃ to form a dense coating layer. This patent constructs a stable Ti-O-Si chemical bond network at the TiO2 interface using a silane coupling agent, providing nucleation sites for subsequent SiO2 deposition. During the low-temperature drying stage (≤150℃), this pre-constructed chemical anchoring structure can effectively induce directional dehydration and condensation of SiO2 molecular chains, and drive the SiO2 network to self-densify and shrink using capillary pressure, thereby obtaining a dense, continuous, and acid-resistant inorganic coating layer under extremely mild conditions, significantly reducing production energy consumption and equipment requirements.

[0018] (3) Ultra-high reflectivity and excellent optical performance: Thanks to the perfect mononuclear core-shell structure and dense low-refractive-index SiO2 shell (n≈1.45), the material prepared in this invention optimizes the refractive index gradient between the high-refractive-index TiO2 core (n≈2.7) and the medium to the greatest extent, enhancing the Mie scattering effect. Compared with aggregated pigments, its light reflection efficiency in photovoltaic glass inks is significantly improved, which helps to improve the power generation gain of photovoltaic modules.

[0019] (4) Inhibiting photocatalytic activity and extending module lifespan: The dense and complete SiO2 insulating coating layer formed by this invention completely blocks the contact between TiO2 and the glass network structure, effectively inhibiting the photocatalytic activity of TiO2 and solving the problems of coating yellowing and decreased adhesion. At the same time, the dense inorganic shell layer blocks the electron migration channel, which can effectively reduce the potential-induced degradation (PID) of photovoltaic modules and significantly extend the service life of modules in complex outdoor environments.

[0020] (5) Low cost and easy to scale up: The present invention adopts all-liquid phase chemical synthesis, which requires simple equipment, cheap and readily available raw materials, mild process conditions, and is easy to realize large-scale industrial production, with extremely high economic benefits and application prospects.

[0021] The coating of this invention, with its excellent acid resistance and reflective properties, not only enhances the power generation gain of the module, but also effectively fills the technological gap in high-end photovoltaic inks in China, reduces the industry's dependence on external supply chains, and has good social benefits and market competitiveness. Attached Figure Description

[0022] Figure 1 This is a TEM image of the TiO2@SiO2 core-shell structure powder obtained in Example 1 of this invention; Figure 2 This is a TEM image of the TiO2@SiO2 core-shell structure powder obtained in Example 2 of this invention; Figure 3 This is a TEM image of the TiO2@SiO2 core-shell structure powder obtained in Example 3 of this invention; Figure 4 The images show the reflectivity test results of the coatings after sintering and cooling in Examples 1, 2, and 3. Figure 5 This is an image showing the appearance morphology of the photovoltaic glass ink in Example 2; Figure 6 This is a test diagram of the adhesion of photovoltaic glass ink in Example 2. Detailed Implementation

[0023] To further illustrate the present invention, the technical means and effects adopted to achieve the intended purpose of the invention, the present invention will be described in detail below with reference to preferred embodiments: Example 1

[0024] A low-temperature preparation method for TiO2@SiO2 core-shell structured materials, characterized by comprising the following steps: Step 1: According to the mass ratio of rutile TiO2, sodium hexametaphosphate, water, and silane coupling agent 1:0.005:15:0.01, first add rutile and sodium hexametaphosphate to water for ultrasonic treatment and stirring dispersion to obtain TiO2 aqueous suspension. Then, add silane coupling agent-ethanol dilution solution dropwise to the stirred TiO2 aqueous suspension using a flow pump. After the addition is complete, adjust the pH value to the corresponding value with dilute hydrochloric acid. Continue stirring and aging for 1 hour, then wash with ethanol, filter, and freeze dry to obtain highly dispersed active TiO2 powder. Step 2: Add the highly dispersed active TiO2 powder obtained in Step 1 to a water-ethanol mixed solution and stir to disperse it, thereby obtaining a TiO2 water-ethanol suspension. Then, according to the mass ratio of highly dispersed active TiO2 powder to tetraethyl orthosilicate 1:0.16, add the tetraethyl orthosilicate-ethanol dilution to the stirred TiO2 water-ethanol suspension using a gradient dropwise process. After the dropwise addition is complete, adjust the pH value to the appropriate value with ammonia water. Then, after stirring and aging, washing, and low-temperature drying, obtain stable TiO2@SiO2 core-shell structure powder.

[0025] In step two, the gradient dripping process involves pausing for 5 minutes after each drop of 25% of the total volume of the tetraethyl orthosilicate-ethanol diluent is added, and then continuing to add at a rate of 0.1 ml / min. This cycle is repeated until all the drops are added.

[0026] In step one, the mass ratio of silane coupling agent to ethanol in the silane coupling agent-ethanol dilution solution is 1:3; the average size of the highly dispersed active TiO2 powder particles is 350 nm.

[0027] The ultrasonic treatment time in step one is 15 min, the stirring time is 15 min, the dropping rate of the silane coupling agent-ethanol dilution is 0.2 ml / min, and the pH value is 4.

[0028] In step two, the volume ratio of water to ethanol in the water-ethanol mixed solution is 1:3, the volume ratio of ethanol to tetraethyl orthosilicate in the tetraethyl orthosilicate-ethanol dilution is 4:1, the pH value is 9, the stirring and aging time is 10 hours, the drying temperature is 150°C, and the drying time is 10 hours.

[0029] The method for applying the product obtained by the aforementioned method is characterized by comprising the following steps: Step 1: According to the glass flux formula K2O 0mol%, Na2O 2mol%, CaO 0mol%, BaO 0mol%, ZnO 46mol%, B2O3 18mol%, Bi2O3 16mol%, SiO2 16mol%, Al2O3 2mol%, the raw materials are mixed, melted and cooled to obtain ZnO-B2O3-Bi2O3-SiO2 glass frit. The glass frit is then crushed, ball-milled and passed through a 250-mesh sieve to obtain low melting point glass powder. Step 2: Mix low melting point glass powder, ink oil and TiO2@SiO2 core-shell structure powder in a certain mass ratio, grind and pass through a 250-mesh sieve to obtain glass ink; Step 3: The glass ink obtained in Step 2 is printed onto a glass substrate using a 200-mesh screen printing machine. The glass substrate is then fired at 750°C and held at the highest temperature for 90 seconds to obtain glass with an inorganic high-reflectivity coating.

[0030] The melting process in step one is carried out at a temperature of 1280℃ for 4 hours; the resulting low-melting-point glass powder has a coefficient of thermal expansion α of 5.26 × 10⁻⁶ at room temperature to 300℃. -6 K -1 Softening temperature T f The temperature is 595℃.

[0031] In step two, the mass percentages of low-melting-point glass powder, ink oil, and TiO2@SiO2 core-shell structure powder are 65:16:19; the ink oil is a water-based ink oil.

[0032] The water-based ink oil comprises the following components by weight percentage: 15% water-based acrylic resin, 10% polyvinyl alcohol, 5% propylene glycol, 0.1% polyether-modified siloxane, 0.1% ammonia, and the balance being water.

[0033] In step three, the ink adhesion performance of the inorganic high reflectivity coating was tested to be (ISO) level 1, with a light reflectivity range of 90.2%. The ink showed no cracking or peeling after acid resistance testing.

[0034] Figure 1 TEM images of TiO2@SiO2 core-shell structured powder were obtained. The images clearly show that the SiO2 shell is dense, continuous, and uniformly coated on the surface of the TiO2 particles. The measured coating thickness is 5.4 nm, which deviates from the target thickness of 5 nm by 8%.

[0035] Figure 4 The figures show the reflectance test results for TiO2@SiO2 core-shell structured material as white pigment. As can be seen from the figures, the reflectance of this embodiment is 90.2%. Example 2

[0036] A low-temperature preparation method for TiO2@SiO2 core-shell structured materials, characterized by comprising the following steps: Step 1: According to the mass ratio of rutile TiO2, sodium hexametaphosphate, water, and silane coupling agent 1:0.01:20:0.02, first add rutile and sodium hexametaphosphate to water for ultrasonic treatment and stirring dispersion to obtain TiO2 aqueous suspension. Then, add silane coupling agent-ethanol dilution solution dropwise to the stirred TiO2 aqueous suspension using a flow pump. After the addition is complete, adjust the pH value to the corresponding value with dilute hydrochloric acid. Continue stirring and aging for 2 hours, then wash with ethanol, filter, and freeze dry to obtain highly dispersed active TiO2 powder. Step 2: Add the highly dispersed active TiO2 powder obtained in Step 1 to a water-ethanol mixed solution and stir to disperse it, thereby obtaining a TiO2 water-ethanol suspension. Then, according to the mass ratio of highly dispersed active TiO2 powder to tetraethyl orthosilicate 1:1.54, add the tetraethyl orthosilicate-ethanol dilution to the stirred TiO2 water-ethanol suspension using a gradient dropwise process. After the dropwise addition is complete, adjust the pH value to the appropriate value with ammonia water. Then, after stirring and aging, washing, and low-temperature drying, obtain stable TiO2@SiO2 core-shell structure powder.

[0037] In step two, the gradient dripping process involves pausing for 10 minutes after each drop of 25% of the total volume of the tetraethyl orthosilicate-ethanol diluent is added, and then continuing to add at a rate of 0.7 ml / min. This cycle is repeated until all the drops are added.

[0038] In step one, the mass ratio of silane coupling agent to ethanol in the silane coupling agent-ethanol dilution solution is 1:5; the average size of the highly dispersed active TiO2 powder particles is 350 nm.

[0039] The ultrasonic treatment time in step one is 20 min, the stirring time is 20 min, the dropping rate of the silane coupling agent-ethanol dilution is 0.5 ml / min, and the pH value is 6.

[0040] In step two, the volume ratio of water to ethanol in the water-ethanol mixed solution is 1:5, the volume ratio of ethanol to tetraethyl orthosilicate in the tetraethyl orthosilicate-ethanol dilution is 4:1, the pH value is 10, the stirring and aging time is 16h, the drying temperature is 200℃, and the drying time is 15h.

[0041] The method for applying the product obtained by the aforementioned method is characterized by comprising the following steps: Step 1: According to the glass flux formula K2O 6mol%, Na2O 6mol%, CaO 4mol%, BaO 3mol%, ZnO2 8mol%, B2O3 15mol%, Bi2O3 2mol%, SiO2 35mol%, Al2O3 1mol%, the raw materials are mixed, melted and cooled to obtain ZnO-B2O3-Bi2O3-SiO2 glass frit. The glass frit is then crushed, ball-milled and passed through a 250-mesh sieve to obtain low melting point glass powder. Step 2: Mix low melting point glass powder, ink oil and TiO2@SiO2 core-shell structure powder in a certain mass ratio, grind and pass through a 250-mesh sieve to obtain glass ink; Step 3: The glass ink obtained in Step 2 is printed onto a glass substrate using a 200-mesh screen printing machine. The glass substrate is then fired at 670°C and held at the highest temperature for 200 seconds to obtain glass with an inorganic high-reflectivity coating.

[0042] The melting process in step one is carried out at a temperature of 1200℃ for 2 hours; the resulting low-melting-point glass powder has a coefficient of thermal expansion α of 8.96 × 10⁻⁶ at room temperature to 300℃. -6 K -1 Softening temperature T f It is 500℃.

[0043] In step two, the mass percentages of low-melting-point glass powder, ink oil, and TiO2@SiO2 core-shell structure powder are 45:15:40; the ink oil is a water-based ink oil.

[0044] The water-based ink oil comprises the following components by weight percentage: 35% water-based acrylic resin, 5% polyvinyl alcohol, 15% propylene glycol, 1% polyether-modified siloxane, 0.5% ammonia, and the balance being water.

[0045] In step three, the ink adhesion performance of the inorganic high reflectivity coating was tested to be (ISO) level 1, with a light reflectivity range of 95.1%. The ink showed no cracking or peeling after acid resistance testing.

[0046] Figure 2 TEM images of TiO2@SiO2 core-shell structured powder were obtained. As can be seen from the image, the SiO2 shell is dense, continuous and uniformly coated on the surface of TiO2 particles. The measured coating thickness is 37.2 nm, which deviates from the target thickness of 40 nm by 7%.

[0047] Figure 4 The figures show the reflectance test results for TiO2@SiO2 core-shell structured material as white pigment. As can be seen from the figures, the reflectance of this embodiment is 95.1%.

[0048] Figure 5 The surface morphology of the coating is shown to be uniform and smooth with no obvious defects, exhibiting high whiteness and good surface quality.

[0049] Figure 6 These are the adhesion test results. The results show that the coating adhesion level reaches ISO 1, exhibiting excellent adhesion performance. Example 3

[0050] A low-temperature preparation method for TiO2@SiO2 core-shell structured materials, characterized by comprising the following steps: Step 1: According to the mass ratio of rutile TiO2, sodium hexametaphosphate, water, and silane coupling agent 1:0.008:18:0.015, rutile and sodium hexametaphosphate are first added to water for ultrasonic treatment and stirring dispersion to obtain TiO2 aqueous suspension. Then, silane coupling agent-ethanol dilution is added dropwise to the stirred TiO2 aqueous suspension using a flow pump. After the addition is complete, the pH value is adjusted to the appropriate value with dilute hydrochloric acid. After stirring and aging for 1.5 hours, the mixture is washed with ethanol, filtered, and freeze-dried to obtain highly dispersed active TiO2 powder. Step 2: Add the highly dispersed active TiO2 powder obtained in Step 1 to a water-ethanol mixed solution and stir to disperse it, thereby obtaining a TiO2 water-ethanol suspension. Then, according to the mass ratio of highly dispersed active TiO2 powder to tetraethyl orthosilicate 1:0.69, add the tetraethyl orthosilicate-ethanol dilution to the stirred TiO2 water-ethanol suspension using a gradient dropwise process. After the dropwise addition is complete, adjust the pH value to the appropriate value with ammonia water. Then, after stirring and aging, washing, and low-temperature drying, obtain stable TiO2@SiO2 core-shell structure powder.

[0051] In step two, the gradient dripping process involves pausing for 8 minutes after each drop of 25% of the total volume of the tetraethyl orthosilicate-ethanol diluent is added, and then continuing to add at a rate of 0.5 ml / min. This cycle is repeated until all the drops are added.

[0052] In step one, the mass ratio of silane coupling agent to ethanol in the silane coupling agent-ethanol dilution solution is 1:4; the average size of the highly dispersed active TiO2 powder particles is 350 nm.

[0053] The ultrasonic treatment time in step one is 18 min, the stirring time is 18 min, the dropping rate of the silane coupling agent ethanol dilution is 0.3 ml / min, and the pH value is 5.

[0054] In step two, the volume ratio of water to ethanol in the water-ethanol mixed solution is 1:8, the volume ratio of ethanol to tetraethyl orthosilicate in the tetraethyl orthosilicate-ethanol dilution is 4:1, the pH value is 9.5, the stirring and aging time is 14 hours, the drying temperature is 180℃, and the drying time is 13 hours.

[0055] The method for applying the product obtained by the aforementioned method is characterized by comprising the following steps: Step 1: According to the glass flux formula of K2O 2mol%, Na2O 3mol%, CaO 3mol%, BaO 2mol%, ZnO 30mol%, B2O3 17mol%, Bi2O3 17mol%, SiO2 24.5mol%, Al2O3 1.5mol%, the raw materials are mixed, melted and cooled to obtain ZnO-B2O3-Bi2O3-SiO2 glass frit. The glass frit is then crushed, ball-milled and passed through a 250-mesh sieve to obtain low melting point glass powder. Step 2: Mix low melting point glass powder, ink oil and TiO2@SiO2 core-shell structure powder in a certain mass ratio, grind and pass through a 250-mesh sieve to obtain glass ink; Step 3: The glass ink obtained in Step 2 is printed onto a glass substrate using a 200-mesh screen printing machine. The glass substrate is then fired at 720°C and held at the highest temperature for 150 seconds to obtain glass with an inorganic high-reflectivity coating.

[0056] The melting process in step one is carried out at a temperature of 1250℃ for 3 hours; the resulting low-melting-point glass powder has a coefficient of thermal expansion α of 7.21 × 10⁻⁶ at room temperature to 300℃. -6 K -1 Softening temperature T f It is 556℃.

[0057] In step two, the mass percentages of low-melting-point glass powder, ink oil, and TiO2@SiO2 core-shell structure powder are 46:32:22; the ink oil is a water-based ink oil.

[0058] The water-based ink oil comprises the following components by weight percentage: 22% water-based acrylic resin, 8% polyvinyl alcohol, 13% propylene glycol, 0.6% polyether-modified siloxane, 0.3% ammonia, and the balance being water.

[0059] In step three, the ink adhesion performance of the inorganic high reflectivity coating was tested to be (ISO) level 1, with a light reflectance range of 92.3%. The ink showed no cracking or peeling after acid resistance testing.

[0060] Figure 3 TEM images of TiO2@SiO2 core-shell structured powder were obtained. As can be seen from the images, the SiO2 shell is dense, continuous and uniformly coated on the surface of TiO2 particles. The measured coating thickness is 19.4 nm, which deviates from the target thickness of 20 nm by 3%.

[0061] Figure 4 The figures show the reflectance test results for TiO2@SiO2 core-shell structured material as white pigment. As can be seen from the figures, the reflectance of all samples is above 90%, with the highest reaching 92.3% in this embodiment.

[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the principles and spirit of the present invention are included within the protection scope of the present invention.

Claims

1. A low-temperature preparation method for TiO2@SiO2 core-shell structured materials, characterized in that... Includes the following steps: Step 1: According to the mass ratio of rutile TiO2, sodium hexametaphosphate, water, and silane coupling agent 1:0.005~0.01:15~20:0.01~0.02, first add rutile TiO2 and sodium hexametaphosphate to water for ultrasonic treatment and stirring dispersion to obtain TiO2 aqueous suspension. Then, add silane coupling agent-ethanol dilution solution dropwise to the stirred TiO2 aqueous suspension using a flow pump. After the addition is complete, adjust the pH value to the corresponding value with dilute hydrochloric acid, continue stirring and aging for 1~2 hours, wash with ethanol, filter, and freeze dry to obtain highly dispersed active TiO2 powder. Step 2: Add the highly dispersed active TiO2 powder obtained in Step 1 to a water-ethanol mixed solution and stir to disperse it, thereby obtaining a TiO2 water-ethanol suspension. Then, according to the mass ratio of highly dispersed active TiO2 powder to tetraethyl orthosilicate 1:0.16-1.54, add the tetraethyl orthosilicate-ethanol dilution to the stirred TiO2 water-ethanol suspension using a gradient dropwise process. After the dropwise addition is complete, adjust the pH value to the appropriate value with ammonia water. Then, after stirring and aging, washing, and low-temperature drying, obtain stable TiO2@SiO2 core-shell structure powder. In step two, the gradient dripping process involves pausing for 5 to 10 minutes after each drop of 25% of the total volume of the tetraethyl orthosilicate-ethanol diluent is added, and then continuing to add at a rate of 0.1 to 0.7 ml / min. This cycle is repeated until all the drops are added. In step one, the mass ratio of silane coupling agent to ethanol in the silane coupling agent-ethanol dilution solution is 1:3-5; the average size of the highly dispersed active TiO2 powder particles is 350 nm. The ultrasonic treatment time in step one is 15-20 min, the stirring time is 15-20 min, the dropping rate of the silane coupling agent-ethanol dilution is 0.2-0.5 ml / min, and the pH value is 4-6. In step two, the volume ratio of water to ethanol in the water-ethanol mixed solution is 1:3 to 8, the volume ratio of ethanol to tetraethyl orthosilicate in the tetraethyl orthosilicate-ethanol dilution is 4:1, the pH value is 9 to 10, the stirring and aging time is 10 to 16 hours, the drying temperature is 150 to 200°C, and the drying time is 10 to 15 hours.

2. The application of the article obtained by the method according to claim 1, characterized in that: Includes the following steps: Step 1: According to the glass flux formula, K2O 0-6mol%, Na2O 2-6mol%, CaO 0-4mol%, BaO 0-3mol%, ZnO 28-46mol%, B2O3 15-18mol%, Bi2O3 2-17mol%, SiO2 16-35mol%, Al2O3 1-2mol%, the raw materials are mixed, melted, and cooled to obtain ZnO-B2O3-Bi2O3-SiO2 glass frit. The glass frit is then crushed, ball-milled, and passed through a 250-mesh sieve to obtain low-melting-point glass powder. Step 2: Mix low melting point glass powder, ink oil and TiO2@SiO2 core-shell structure powder in a certain mass ratio, grind and pass through a 250-mesh sieve to obtain glass ink; Step 3: The glass ink obtained in Step 2 is printed onto a glass substrate using a 200-mesh screen printing machine. The glass substrate is then fired at 670-750°C and held at the highest temperature for 90-200 seconds to obtain glass with an inorganic high reflectivity coating. In step two, the mass percentages of low-melting-point glass powder, ink oil, and TiO2@SiO2 core-shell structure powder are 45-65:15-32:19-40; the ink oil is a water-based ink oil.

3. The application according to claim 2, characterized in that: The melting process in step one is carried out at a temperature of 1200–1280℃ for 2–4 hours; the resulting low-melting-point glass powder has a coefficient of thermal expansion α of 5.26–8.96 × 10⁻⁶ at room temperature to 300℃. -6 K -1 Softening temperature T f The temperature ranges from 500 to 595℃.

4. The application according to claim 2, characterized in that: The water-based ink oil comprises, by weight percentage, the following components: 15-35% water-based acrylic resin, 5-10% polyvinyl alcohol, 5-15% propylene glycol, 0.1-1% polyether-modified siloxane, 0.1-0.5% ammonia, with the balance being water.

5. The application according to claim 2, characterized in that: The reflectivity range of the inorganic high-reflectivity coating in step three is 90.2% to 95.1%.

Citation Information

Patent Citations

  • Method for preparing carbon black inclusion pigment in situ by nonhydrolytic sol-gel process

    CN102433033B

  • Preparation method of ceramic-coated pigment with mononuclear coating and controllable coating layer thickness and product prepared by preparation method

    CN118063978A

  • Method for wrapping high-refractive-index ceramic powder with low-refractive-index product layer and ceramic material

    CN121063948A

  • Polyvinyl alcohol fiber-doped polyacrylic acid type environmental-protection water-based ink

    CN104774501A

  • Preparation method of spherical nano silica-coated hexagonal boron nitride composite powder

    CN104974817A